Thinking Narratively : Between Novel-Essay and Narrative Essay. - Fusillo, Massimo. (Transcodification: Arts, Languages and Media Series, 2022)
The series explores the complexity and the interconnections of arts and languages by merging, comparing and contrasting themes from different sources, methodologies or fields of studies. Its main results derive from the "Arts, Languages, and Media: Translation and Transcodification" project but it is also open to monographs and edited volumes arisen from different contexts and projects.